SHYNESS DITINJAU DARI FIVE GUIDANCE NEEDS PADA REMAJA SMA DI MAKASSAR - Jennifer Chikita (Fakultas Psikologi Universitas Hang Tuah, 2019)
his study aims to determine the relationship between 5 guidance needs, namely educational needs, vocational needs, physic needs, social needs, and psychological needs with shyness among Senior High School adolescents in Makassar. A total of 415 Senior High School adolescent as the subject in this study by using accidental sampling technique. Inventory that used to assess shyness is Ridfah’s shyness inventory and guidance needs inventory to assess guidance needs. The Result showed that shyness have significant relationship with guidance needs and all the areas, which are educational needs, vocational needs, physic needs, psychological needs and social needs. Results revealed that the among the five areas of guidance needs, social needs have the highest correlation value to shyness in individuals with r = -0,448. This study revealed that the need for guidance needs is measured in order to optimize the guidance to be provided.